Detection of subarachnoid haemorrhage on early CT: is lumbar puncture still needed after a negative scan?. Issue 3 (March 1995) - van der Wee, N; Rinkel, G J; Hasan, D; van Gijn, J
Abstract : Computed tomography may be normal in up to 5% of patients who are investigated within one or two days after subarachnoid haemorrhage. This study investigated the need for further diagnostic evaluation after a normal CT scan was found very early (within 12 hours) in patients suspected of subarachnoid haemorrhage. A consecutive series of 175 patients with sudden headache and a normal neurological examination who had first CT within 12 hours after the onset of headache were investigated. The patients with normal CT underwent lumbar puncture, but not earlier than 12 hours after the event. Computed tomography showed subarachnoid blood in 117 patients, and was normal in 58. Spectrophotometric analysis of CSF gave evidence for a subarachnoid haemorrhage in two of these 58 patients (3%; 95% confidence interval (95% CI) 0.4-12%); a ruptured aneurysm was found in both. Thus CT was normal in two of 119 patients with a definite subarachnoid haemorrhage (2%; 95% CI 0.2-6%). It is concluded that in patients with sudden headache but normal CT a deferred lumbar puncture is necessary to rule out subarachnoid haemorrhage, even if CT is performed within 12 hours after the onset of symptoms.